Estudio de factibilidad para la creación de un punto de venta de “Fertisa” del grupo Wong en la parroquia Patricia Pilar, año 2013 - Rosado Limones, Elena Mariuxi (2013)
This work was carried out at the Parish Patricia Pillar, canton Good Faith, Province of the Rivers, 45 km from Santo Domingo de los Colorados; limit between the provinces of the rivers and Santo Domingo of the Tsáchilas, orography of irregular relief. Its topography is more or less low whose maximum height does not exceed 470 meters above sea level. The goal was to fulfill the agreed objectives: general objective perform a feasibility study for the creation of a point-of-sale "FERTISA" of the group Wong in the parish Patricia Pillar province of the rivers, and their specific objectives (a) Diagnose through a study of market the need to create a point-of-sale in the parish Fertisa Patricia Pillar of the canton good faith, in the province of the Rivers, (b) Develop a technical study and financial viable to allow the relevant investment for the realization of the project, (c) to determine the economic and financial profitability of this feasibility study. The market study stipulated an offer of 585,727 agricultural inputs/year; and that, in the face of the established demand by the areas of crop will require 836,754 inputs/year, determined an interesting market space to be treated, same justifies the size of the project, because this will cover 15% of the projected future demands for the period 2014-2018; quantified among 128,023 units of inputs in the first year and 144.091 by the end of the life cycle of the project; the investment in fixed assets and deferred is $ 290.100.52; fixed costs $ 37,645.23 and the variables $3’218,481.90. Revenue in the first year are $ 3’603.987.40; the cash flow generated during the first year is $ 806,093.03; the point of equilibrium corresponds to the marketing of 43.268 units of inputs/year, which the monetary represent $ 1’261,417.06; the benefit cost ratio is 1.11; the VAN funds$ 806,093.03 and the IRR equivalent to 76% surpassing the market rate. The project is also sensitive, supports a decrease in sales up to a 5.79 % and an increase in the cost of 6.42 %; causes an impact on the employment generating the integration of 5 new working places.